A review of challenges in learning Chinese characters among non-native learners in Malaysia - Chua Hui Wen; Tan Tse Guan; Lin Chia Ying (Discovery Publication, 2015)
Chinese language is totally different compared to others languages found in Malay and English languages. These languages use alphabets to form words. Chinese language consists of Chinese character that has three compounds which are form, sound and meaning. Hence, learners require to spare more time to remember the three compounds of each character during their learning process. In this paper, challenges in learning Chinese characters in Malaysia and integration of technology that was carried out overcome it will be discussed in order to improve learner's language learning.